Pengaruh Persepsi Kegunaan dan Persepsi Kemudahan Penggunaan terhadap Sikap Penggunaan Teknologi pada Pengguna Instagram di Indonesia (Studi pada Followers Akun Kementerian Pariwisata @Indtravel) - Arry Widodo; Ayunabillah Syahvitrie Azdy Putri (Jurnal Sekretaris dan Administrasi Bisnis, 2017)
Global technological advances makes the internet as a necessity for the modern society. The development of mobile technology offers users the ease to access the desired content in social media. Social media has content that contains information, created by people who use publishing technology which very accessible in order to facilitate communication, influence and interact with others and with the general public. It is utilized by the Ministry of Tourism of the Republic of Indonesia to create an Instagram account named @indtravel as a provider of Indonesian tourism information. In this study, the attitude of the use of technology will be measured through the perception of usability and perception of ease of use. Data analysis techniques used are quantitative descriptive analysis techniques and multiple linear regression analysis. The population in this study is 327,000 with a sample of 100 people. The results showed that perceived usefulness is on the good category, perceived ease of use is on the good category, and attitude toward using is on the good category as well. Partially, perceived usefulnesss (X1) and perceived ease of use (X2) has a significant influence on the attitude toward using (Y). Simultaneously, perceived usefulness (X1) and perceived ease of use (X2) has a significant influence on the attitude toward using (Y). Keywords: Social Media, Technology Acceptance Model (TAM)